Recreational 3, 4-methylenedioxy-N-methylamphetamine (MDMA) or 'ecstasy' and self-focused compassion: Preliminary steps in the development of a therapeutic psychopharmacology of contemplative practices. (September 2015) - Kamboj, Sunjeev K; Kilford, Emma J; Minchin, Stephanie; Moss, Abigail; Lawn, Will; Das, Ravi K; Falconer, Caroline J; Gilbert, Paul; Curran, H Valerie; Freeman, Tom P
3, 4-methylenedioxy- N -methylamphetamine (MDMA) produces diverse pro-social effects. Cognitive training methods rooted in Eastern contemplative practices also produce these effects through the development of a compassionate mindset. Given this similarity, we propose that one potential mechanism of action of MDMA in psychotherapy is through enhancing effects on intra personal attitudes (i.e. pro-social attitudes towards the self ). We provide a preliminary test of this idea. Recreational MDMA (ecstasy) users were tested on two occasions, having consumed or not consumed ecstasy. Self-critical and self-compassionate responses to self-threatening scenarios were assessed before (T1) and after (T2) ecstasy use (or non-use), and then after compassionate imagery (T3). Moderating roles of dispositional self-criticism and avoidant attachment were examined. Separately, compassionate imagery and ecstasy produced similar sociotropic effects, as well as increases in self-compassion and reductions in self-criticism. Higher attachment-related avoidance was associated with additive effects of compassionate imagery and ecstasy on self-compassion. Findings were in line with MDMA's neuropharmacological profile, its phenomenological effects and its proposed adjunctive use in psychotherapy. However, although conditions were balanced, the experiment was non-blind and MDMA dose/purity was not determined. Controlled studies with pharmaceutically pure MDMA are still needed to test these effects rigorously.